Channelling mobilities migration and globalisation in the Suez Canal region and beyond, 1869-1914 - Huber, Valeska 1980- (Cambridge University Press, 2013)
The history of globalisation is usually told as a history of shortening distances and acceleration of the flows of people, goods and ideas. Channelling Mobilities refines this picture by looking at a wide variety of mobile people passing through the region of the Suez Canal, a global shortcut opened in 1869. As an empirical contribution to global history, the book asks how the passage between Europe and Asia and Africa was perceived, staged and controlled from the opening of the Canal to the First World War, arguing that this period was neither an era of unhampered acceleration, nor one of hardening borders and increasing controls. Instead, it was characterised by the channelling of mobilities through the differentiation, regulation and bureaucratisation of movement. Telling the stories of tourists, troops, workers, pilgrims, stowaways, caravans, dhow skippers and others, the book reveals the complicated entanglements of empires, internationalist initiatives and private companies